1993
DOI: 10.1021/jm00075a009
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and anti-HIV activity of O-acylated heparin and dermatan sulfate derivatives with low anticoagulant effect

Abstract: In order to increase the ratio of anti-HIV activity to anticoagulant activity, glycosaminoglycan derivatives selectively substituted at OH and/or COOH groups were prepared. Standard heparin, heparin fragments, or dermatan sulfate were converted to their tributylammonium or tetrabutylammonium salts. Their selective O-acylation to various (controlled) degrees was carried out in a homogeneous way in N,N-dimethylformamide using carboxylic acid anhydrides and 4-(dimethylamino)pyridine as catalyst. Esterification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Dextran sulfate, upon intravenous administration, produces thrombocytopenia (164). Sulfated polymers are also notorious for their anticoagulant activity, but as has been demonstrated with periodate-treated heparin (19) and O-acylated heparin (63), this problem can be overcome by appropriate chemical modifications.…”
Section: Anti-hiv Agents Virus Adsorption Inhibitorsmentioning
confidence: 99%
“…Dextran sulfate, upon intravenous administration, produces thrombocytopenia (164). Sulfated polymers are also notorious for their anticoagulant activity, but as has been demonstrated with periodate-treated heparin (19) and O-acylated heparin (63), this problem can be overcome by appropriate chemical modifications.…”
Section: Anti-hiv Agents Virus Adsorption Inhibitorsmentioning
confidence: 99%
“…Using this procedure, the plasma half-life of heparin in humans has been found to be approximately 35 min (after iv injection of 23 mg heparin) (Dawes et al, 1986). However, the anti-HIV activity and anticoagulant effects of sulfated polymers are not necessary correlated (Baba et al, 1990a;Barzu et al, 1993).…”
Section: Pharmacokinetic Profilementioning
confidence: 99%
“…Shortly after the identification and isolation of the virus responsible for the acquired immune deficiency syndrome (AIDS) (subsequently named the human immunodeficiency virus, HIV), several groups, following a suggestion of De Clercq (1986), demonstrated that heparin and other polysulfates are potent and selective inhibitors of HIV-1 replication in cell culture (Ito et el., 1987(Ito et el., , 1991suya et el., 1988;Mizumoto et ei., 1988;Yoshida et al, 1988;Hirabayashi et el., 1989;Jurkiewicz et el., 1989;Sugawara et al, 1989;Tochikura et al, 1989;Anand et el., 1990a,b;Kaneko et al, 1990;Montefiori et al, 1990;Weiler et al, 1990;Schols et sl., 1990aSchols et sl., , 1991Von Briesen et al, 1990;Aoki et al, 1991;Bagasra et al, 1988Bagasra et al, , 1991Sosa et al, 1991;Handa et al, 1991;Hatanaka et al, 1991;McClure et al, 1991;Moriya et al, 1991Moriya et al, , 1993Otake et al, 1991Otake et al, , 1994Witvrouw et al, 1991Witvrouw et al, , 1992Witvrouw et al, , 1994Mizuno et al, 1992;Uryu et al, 1992;Barzu et al, 1993;Beutler et al, 1993;Damonte et el., 1994). Several polysulfates were also found to be active against a wide variety of enveloped viruses (Baba et el., 1988c;De Clercq, 1990, 1993;Andrei et el., 1991;Schols et al...…”
Section: Introductionmentioning
confidence: 99%
“…For example, Petitou et al [12] selectively introduced acyl groups into heparin and its fragments. The measurements of anticoagulant and anti-HIV activities of these compounds indicated that their anti-HIV activities did not differ markedly from that of heparin, although their anticoagulant activities were much lower [13]. O -Acylated low-molecular-weight carrageenans were prepared.…”
Section: Introductionmentioning
confidence: 99%